2
$\begingroup$

Prove that $p_2(n) = \left \lfloor{\frac{n}{2}}\right \rfloor+1$ using the identity $$\frac{1}{(1-x)(1-x^2)}=\frac{1}{2}\left(\frac{1}{(1-x)^2}\right)+\frac{1}{2}\left(\frac{1}{1-x^2}\right)$$

where $p_k(n)$ is the number of partitions of an integer $n$ into a most $k$ parts. The generating function $P_k(x)$ of $\{p_k(n)\}$ is $$P_k(x) = \frac{1}{\prod_{r=0}^{k}(1-x^k)}$$ Therefore, the generating function $P_2(x)$ of ${p_2(n)}$ is $$P_2(x) = \frac{1}{(1-x)(1-x^2)}$$ Now I see here that we can use the identity given above, but I am confused of how to apply it to prove the desired statement.

$\endgroup$
  • $\begingroup$ Find the Taylor series for $\frac{1}{(1-x)^2}$ and $\frac{1}{1-x^2}$ and go from there. $\endgroup$ – steven gregory May 23 '18 at 11:18
0
$\begingroup$

Note that $$\begin{align}\frac{4}{(1-x)(1-x^2)}&=\frac{1}{1+x}+\frac{1}{1-x}+\frac{2}{(1-x)^2}\\ &=\frac{1}{1+x}+\frac{1}{1-x}+\frac{d}{dx}\left(\frac{2}{1-x}\right)\\ &=\sum_{n=0}^{\infty}(-x)^n+\sum_{n=0}^{\infty}x^n +2\sum_{n=1}^{\infty}nx^{n-1}\\ &=\sum_{n=0}^{\infty}((-1)^n+1+2(n+1))x^n \end{align}$$ Can you take it from here?

$\endgroup$
0
$\begingroup$

You have $$P_2(x) = \frac{1}{2}\left(\frac{1}{(1-x)^2}\right)+\frac{1}{2}\left(\frac{1}{1-x^2}\right) = \frac12 (1-x)^{-2} + \frac12 (1-x^2)^{-1}$$ Now, the generalised binomial expansion is $(1+x)^a = 1 + \frac{a}{1!}x + \frac{a(a-1)}{2!}x^2 + \cdots$

Therefore $$\begin{eqnarray} (1 - x)^{-2} &=& 1 + \frac{(-2)}{1!}(-x) + \frac{(-2)(-3)}{2!}(-x)^2 + \cdots \\ &=& 1 + 2x + 3x^2 + \cdots \end{eqnarray}$$

and $$\begin{eqnarray}(1-x^2)^{-1} &=& 1 + \frac{(-1)}{1!}(-x^2) + \frac{(-1)(-2)}{2!}(-x^2)^2 + \cdots \\ &=& 1 + x^2 + x^4 + \cdots \end{eqnarray}$$

Combine and you're done. It may be helpful to consider separately the cases where $n$ is even vs odd.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.